Supervised optimal on-line compensation for harmonic pollution in electrical networks - Beguery, P.; Gentil, S.; Bonnard, F. (Control engineering practice, 1998)
Harmonic reduction has become one of the major challenges facing electrical distribution. This is a large-size problem, concerned with a nonlinear and noisy system, subject to configuration changes. This paper presents a new adaptive harmonic compensation, whose main originality is its capacity to simultaneously minimise harmonic pollutions at several points. The control space is explored step by step to search for the optimal compensation, without an intermediate identification phase. To prevent problems with local minima, exploratory behaviour is added to simple optimisation. Two search methods – optimisation-directed and exploration directed – are given. Data storage and control supervision problems are also addressed, and some experimental results are discussed.